Kai kurie visuomenės informatizavimo tyrimų metodologiniai aspektai - Gudonienė, Vilija (Knygotyra, 1990)
In the article, an attempt is made to attract attention to the variety of methodological principles in the analysis of some factors of informatization of society. Most of the questions of informatization—such as the information crisis, information industry, information resources, etc.—are bound to technological deterministic explanations, and the aspects of the new electronic technology are amplified, with all problems being reduced to computerization. Using economic methodologies, the question of information value is considered. Economic research on informatization is correlated with attempts to analyze the quantity of information. The conclusion is drawn that most of the principles of analyzing informatization problems are conditioned by already known scientific paradigms.